MaxPHOS Ligand: PH/NH Tautomerism and Rhodium- Catalyzed Asymmetric Hydrogenations - Cristóbal Lecina, Edgar (2014)
MaxPHOS is an active and robust P-stereogenic ligand for asymmetric catalysis. The presence of an NH bridge between the two phosphine moieties allows the NH/PH tautomerism to take place. The neutral ligand, in which the NH form predominates, is an air-sensitive compound. However, protonation of MaxPHOS leads to the stable PH form of the ligand, in which the overall positive charge is distributed on both P centers. This protonation turns the MaxPHOS·HBF4 salt 3 into an airstable compound both in the solid state and in solution. The salt 3 is also a convenient precursor for the preparation of rhodium(I) complexes by direct ligand exchange with the complex [Rh(acac)(cod)]. Finally, the corresponding rhodium(I)-MaxPHOS complex was tested in the asymmetric hydrogenation of a wide range of substrates. The complex proved to be a highly selective and robust system in these reactions.